Interval Walking Training in Order to Control Blood Glucose Level among Older Adults - Dady Iskandar; Agus Setiawan; Mas Agus Eka Pratama (Universitas 'Aisyiyah Bandung, 2025)
Older adults are a vulnerable to elevated bllod glucose levels due to age-related metabolic decline and insufficient physical activity. This community service program aimed to improve knowledge, exercise skills and immediate glycemic response among older adults through health education and guided interval walking training (IWT) as a practical physical activity strategy. The target participants were community-dwelling older adults aged 60-75 years in Banten Province who were able to walk independently. The program employed a participatory health education approach, consisting of educational lectures, visual media presentations, demonstration and supervised IWT practice. Educational media included PowerPoint slides, verbal counseling, and direct exercise guidance by physiotherapists. Program outcomes were evaluated using validated knowledge questionnaires and random blood glucose measurements conducted before and after the activity using calibrated glucometers. Data were analyzed descriptively to compare pre- and post-activity outcomes. The results demontrated a significant improvement in participants’ knowledge score increasing from 62% to 91%, alongside a reduction in average blood glucose levels from 178 mg/dL to 156 mg/dL representing a 12.4% decrease following a single session. Additionally the number of participants with blood glucose levels above 200 mg/dL decrease from 9 to 3 individuals. These findings indicate the community-based health education combined with guided interval walking can enhance awareness, exercise engangement, and short-term blood glucose control in older adults. This program highlights the potential of physiotherapist-led educational interventions as an accesible strategy for promoting activve lifestyles and supporting metabolic health among older populations.